Differences in the Effects of Selective Logging on Amphibian Assemblages in Three West African Forest Types. (5th June 2012) - Ofori‐Boateng, Caleb; Oduro, William; Hillers, Annika; Norris, Ken; Oppong, Samuel K.; Adum, Gilbert B.; Rödel, Mark‐Oliver
Abstract Making generalizations about the impact of commercial selective logging on biodiversity has so far remained elusive. Species responses to logging depend on a number of factors, many of which have not been studied in detail. These factors may include the natural forest conditions (forest types) under which logging impacts are investigated; but this question has so far remained unexamined. In a large‐scale replicate study we aimed at clarifying the relationship between logging and forest types on leaf litter frogs. We contrast three distinct and naturally occurring forest types, including wet evergreen, moist evergreen and semi‐deciduous forests. Selectively logged sites were compared with primary forest sites for each forest type. We found that the response of frog communities to logging varies in different forest types. In the wet evergreen forest, richness was higher in logged forest than primary forest, while diversity measures were not different between logged and primary forest habitats. In the moist evergreen, richness and diversity were higher in selectively logged areas compared with primary forest habitats. In the semi‐deciduous, logged forests were characterized by drastic loss of forest specialists, reduced richness, and diversity. These results indicate that the net effect of logging varies with respect to forest type. Forest types that are characterized by adverse climatic conditions (i.e., low rainfall and protracted dry seasons) are more likely to produce negative effects on leaf litter anuran communities. For comparisons of the impact of logging on species to be effective, future research must endeavor to include details of forest type.